Statistical Problems of Contingency Models in Organizational Behavior - Korman, Abraham K.; Tanofsky, Robert (Academy of Management Journal, 1975)
The article examines some of the methodological and statistical problems of contingency theories of leadership from both of these perspectives. Proper testing and management application of the contingency model requires prior knowledge of parameter values, which can be difficult to obtain. The logic of the contingency model is reviewed. Sales managers are discussed as an example of individuals who require a small amount of product knowledge and little to no supervision to carry out their task, noting that their motivation is not dependent on external incentives.